Sunn Hemp—A Promising Cover Crop in Florida: SL 306/TR003, rev. 9/2015 - Wang, Qingren; Li, Yuncong C.; Klassen, Waldemar; Hanlon, Edward A. (EDIS, 2015)
SL-306 (formerly SS-AGR-96), a 4-page illustrated fact sheet by Yuncong Li, Qingren Wang, Waldemar Klassen, Edward A. Hanlon, Jr., describes this green manure crop that has been grown for centuries in Southeast Asia — origin and distribution, description, uses, production and harvest, and seed production. Includes references. Updated with title change by the UF Department of Soil and Water Sciences, September 2015. Minor revision October 2018. SL 306/TR003: Sunn Hemp—A Promising Cover Crop in Florida (ufl.edu) Previous version: Li, Yuncong, Qingren Wang, Waldemar Klassen, and Edward Hanlon. 2009. “Sunn Hemp - A Cover Crop in Florida”. EDIS 2009 (8). https://journals.flvc.org/edis/article/view/118084.